STUDENTS RESPONSES’ TOWARD THE PRACTICES OF TEACHING VOCABULARY USING ENGLISH SONG - Anisa Anisa; Euis Rina Mulyani (PROJECT (Professional Journal of English Education), 2023)
This study aimed to investige students’ responses to the practice of teaching vocabulary using English song. The subjects of this study were nine students of class VIII SMP Kiansantang Bandung which were held in two meetings. The research design used by researcher in this study was descriptive qualitative. In this study, researchers used data analysis techniques based on Miles and Huberman (1994) involving three steps: data reduction, data display, and drawing conclusions picture / verification. The data shows that the practice of teaching vocabulary using English song received a positive response from students. Most students said that learning vocabulary using song is fun, good, interesting, can generate motivation. However, some students said they experienced difficulty in producing good pronunciation. Keywords:  English Song; Vocabulary